ESTIMATING EQUITY-LINKED LIFE TERM INSURANCE PREMIUM BY BLACK-SCHOLES OPTION PRICING MODEL - HERDY KWEE, JASON
Insurance is a contract between the insurer and the insured. By paying an amount of premium to the insurer, an insurance policy which guarantees the insured will be published. The amount of premium that should be paid is an expectation of the benefit, so the premium depends on the amount of benefit. In traditional life insurance, the benefits provided are constant according to the initial agreement. One variation of this product is called equity-linked (EL) life insurance. Equity-linked life insurance products links benefits to an asset value. To determine the premium for this insurance product, it is necessary to determine the expected benefits, or the expected asset value. One of the versions of this product provides a warranty, ensuring the policyholder does not suffer losses. The benefit model of EL life insurance with a guarantee is similar to the payoff of a European call option model. Therefore, the Black-Scholes option pricing model will be used to determine the expected the benefit of the product. After generating the premium model of EL term life insurance without and with warranty, a numerical simulation will be carried out. The stock data used as a reference is the BBCA's 2021 daily closing share price data, and the Indonesian Mortality Table IV (2019) for calculating the probability of death. From numerical simulations for men and women in the age group of 45, 50, and 55 years with policy terms of 15, 20, 25, and 30, it can be seen that the premiums for men are always higher than those for women. The premium will be higher if the policyholder is getting older and the policy term is longer. When compared, the product with warranty has a higher premium than the one without. When compared to the traditional version, EL life insurance premiums are higher.